2021
DOI: 10.1007/s11760-021-01869-7
|View full text |Cite
|
Sign up to set email alerts
|

Student behavior analysis to measure engagement levels in online learning environments

Abstract: After the COVID-19 pandemic, no one refutes the importance of smart online learning systems in the educational process. Measuring student engagement is a crucial step towards smart online learning systems. A smart online learning system can automatically adapt to learners' emotions and provide feedback about their motivations. In the last few decades, online learning environments have generated tremendous interest among researchers in computer-based education. The challenge that researchers face is how to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…The research achieved the best performance in terms of accuracy among all the reviewed papers that predicted student engagement levels using physiological data. To provide robust and more effective student engagement measures, Altuwairqi et al ( 2021 ) combined learning interaction and physiological data (facial expression data, mouse movement and keystrokes) of students to build a naïve bayes model that predicted student engagement with an accuracy of 95.2%. The accuracy level of the two approaches suggested that automatic student engagement detection can effectively track issues on engagement in learning environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research achieved the best performance in terms of accuracy among all the reviewed papers that predicted student engagement levels using physiological data. To provide robust and more effective student engagement measures, Altuwairqi et al ( 2021 ) combined learning interaction and physiological data (facial expression data, mouse movement and keystrokes) of students to build a naïve bayes model that predicted student engagement with an accuracy of 95.2%. The accuracy level of the two approaches suggested that automatic student engagement detection can effectively track issues on engagement in learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this literature review, the most predominant approach for detecting engagement using physiological data is facial expression tracking. A number of studies (Monkaresi et al, 2017 ; Dubbaka and Gopalan, 2020 ; Mohamad Nezami et al, 2020 ; Altuwairqi et al, 2021 ) analyzed student engagement during interaction with online educational systems using facial expressions. The studies focused on capturing and analyzing facial expressions to identify disengagement and engagement states of students.…”
Section: Discussionmentioning
confidence: 99%
“…The methods in [28,29,30,31] predict an online/offline student 's engagement on an ordinary scale with 3 or more levels. In [28], the engagement is predicted by 3 levels through a naive-Bayes classification model whose inputs are mouse gesture, keystroke, facial expression feature extracted by webcam image. The prediction from PC utilizing behavior and webcam image has the advantage of noninvasiveness and simplicity of implementation.…”
Section: Related Workmentioning
confidence: 99%
“…Other works centered around student emotional state detection analyze and process signals from Electroencephalogram (EEG), Electromyogram (EMG), Electrocardiography (ECG), Electrodermal activity (EDA), heart rate variability, skin temperature, blood volume pulse, respiration, or Electrodermography (EDG)/galvanic skin response (GSR) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Researchers [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] report the use of deep learning and machine learning (ML) techniques for emotion classification. Finally, other techniques rely on emotion recognition via computer vision [ 22 , 41 , 48 , 49 , 50 ], linguistic semantic approaches [ 51 ], and biological features [ 52 ].…”
Section: Introductionmentioning
confidence: 99%